The use of social networking by working people - Školudová Jana (Technická univerzita v Liberci, 2013)
In the dynamically developing market environment of today it is very difficult to do sucessful business and lead a firm towards long-term prosperity. Owners of firms are well aware of the necessity to incorporate tools using the concept of Internet social networks into business, promotion and communication equipment. Thanks to the development of modern technologies, the increase in the use and sharing of multimedia and never ending changes in purchase behaviour the utilization of social networks keeps increasing. The objective of this article is to analyse and define a specific behaviour of working people as users of online social networks, while focusing on the utilization for marketing purposes. The article’s beginning is dedicated to the theorethical basis and to the short introduction of online social networks. The practical part analyses data obtained on the basis of an executed questionairre survey, the definition of a specific use of social netoworks by working people and subsequently the statistical verification of two hypotheses via statistical formulas and corelation analysis. The conclusion sums up the entire issue, including the executed survey, with recommendations for how to use social networks for marketing purposes correctly.
Využívání sociálních sítí pracujícími
Keywords: social networks; working people; customer; sociální sítě; pracující; zákazník